The Potential Impact of COVID-19 Pandemic on the Antenatal Care as Perceived by Non-COVID-19 Pregnant Women: Women’s Experience Research Brief - Malitha Patabendige MBBS, MD (O&G); Madhawa M Gamage MBBS; Asanka Jayawardane MBBS, MD, M.Phil, MRCOG (Journal of Patient Experience, 2021)
We aimed to study the impact of Coronavirus disease 2019 (COVID-19) pandemic on the basic antenatal care received during the. A facility-based descriptive cross-sectional study was conducted and 62 pregnant women were interviewed. A total of 80.6% of mothers were satisfied with the quality of antenatal care they received, ≥ 7 of 10 on visual analogue scales (VAS). The majority of women were not confident to deliver their baby and 58.1% of women showed ≤ 5 of 10 on VAS. Midwife (90.3%) was the commonest source of information. Internet (1.6%) was a poor source. The impact of the COVID-19 pandemic on the quality of antenatal care was significant, and the findings are useful for the policymakers to plan necessary actions.